Induced illusory body ownership in borderline personality disorder - Neustadter, Eli S (Neurosci Conscious, 2019)
One aspect of selfhood that may have relevance for borderline personality disorder (BPD) is variation in sense of body ownership. We employed the rubber hand illusion to manipulate sense of body ownership in BPD. We extended previous research on illusory body ownership in BPD by testing: (i) two illusion conditions: asynchronous and synchronous stimulation, (ii) relationship between illusion experience and BPD symptoms, and (iii) relationship between illusion experience and maladaptive personality traits. We measured illusion strength (questionnaire responses), proprioceptive drift (perceived shift in physical hand position), BPD symptoms (Revised Diagnostic Interview for Borderlines score), and maladaptive personality traits (Personality Inventory for DSM-5) in 24 BPD and 21 control participants. For subjective illusion strength, we found main effects of group (BPD > healthy control, F(1, 43) = 11.94, P = 0.001) and condition (synchronous > asynchronous, F(1, 43) = 22.80, P < 0.001). There was a group × condition interaction for proprioceptive drift (F(1, 43) = 6.48, P = 0.015) such that people with BPD maintained illusion susceptibility in the asynchronous condition. Borderline symptom severity correlated with illusion strength within the BPD group, and this effect was specific to affective (r = 0.45, P < 0.01) and cognitive symptoms (r = 0.46, P < 0.01). Across all participants, trait psychoticism correlated with illusion strength (r = 0.44, P < 0.01). People with BPD are more susceptible to illusory body ownership than controls. This is consistent with the clinical literature describing aberrant physical and emotional experiences of self in BPD. A predictive coding framework holds promise to develop testable mechanistic hypotheses for disrupted bodily self in BPD.